Regenerative Effect of Mesenchymal Stem Cell on Cartilage Damage in a Porcine Model - Sheng-Chuan Lin; Sankar Panthi; Yu-Her Hsuuw; Shih-Hsien Chen; Ming-Ju Huang; Martin Sieber; Yan-Der Hsuuw (Biomedicines, 2023)
Osteoarthritis (OA) is a major public and animal health challenge with significant economic consequences. Cartilage degradation plays a critical role in the initiation and progression of degenerative joint diseases, such as OA. Mesenchymal stem cells (MSCs) have become increasingly popular in the field of cartilage regeneration due to their promising results. The objective of this preclinical study was to evaluate the regenerative effects of mesenchymal stem cells (MSCs) in the repair of knee cartilage defects using a porcine model. Seven healthy LYD breed white pigs, aged 9–10 weeks and weighing approximately 20 ± 3 kg, were used in the experimental protocol. Full-thickness defects measuring 8 mm in diameter and 5 mm in depth were induced in the lateral femoral condyle of the posterior limbs in both knee joints using a sterile puncture technique while the knee was maximally flexed. Following a 1-week induction phase, the pig treatment groups received a 0.3 million/kg MSC transplant into the damaged knee region, while the placebo group received a control solution as a treatment. Magnetic resonance imaging (MRI), computerized tomography (CT), visual macroscopic examination, histological analysis, and cytokine concentration analysis were used to assess cartilage regeneration. The findings revealed that human adipose-derived mesenchymal stem cells (hADSCs) were more effective in repairing cartilage than pig umbilical cord-derived mesenchymal stem cells (pUCMSCs). These results suggest that MSC-based treatments hold promise as a treatment option for cartilage repair, which aid in the treatment of OA. However, further studies with larger sample sizes and longer follow-up periods are required to fully demonstrate the safety and efficacy of these therapies in both animals and humans.